PERANAN PEMERINTAHAN NAGARI SITUJUAH BATUA DALAM PENGELOLAAN BELANJA BIDANG PENANGGULANGAN BENCANA DARURAT MENDESAK NAGARI UNTUK PENANGGULANGAN COVID-19 TAHUN ANGGARAN 2020 - Nurul Aisyah; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Covid-19 is a non-natural disaster that causes many problems. Among them are making people lose their jobs, demanding a reallocation of the budget that has been set, and presenting uncertainty in the running of the government. In the midst of uncertainty due to covid 19, Nagari Situjuah Batua became the best nagari in Limapuluh Kota Regency. This assessment is based on the Regulation of the Minister of Home Affairs concerning the Evaluation of Village and Kelurahan Development, whose evaluation is in the form of evaluation in the government sector which includes the performance of village government, evaluation in the regional sector which includes the field of innovation in response and disaster preparedness, and evaluation in the social sector which includes economic health, security and order. . This research is a descriptive qualitative research with primary data sources and secondary data. Data collection techniques were carried out by interviewing and reviewing the literature. Then the data obtained is analyzed and modified according to the Agile governance principles of the theory used. The first role carried out by the Situjuah Batura government in managing the Covid-19 disaster is to carry out the first principle, namely good enough governance through the activity of forming a Covid-19 task force team with spending of IDR 53,714,000. Furthermore, business driven, through the distribution of direct cash assistance with spending of Rp. 351,000,000. Next is the human focus, through the activities of creating a guard post and sterilizing village social facilities with an expenditure of Rp. 25,605,000. Furthermore, based on quick wins, through the provision of PPE and antiseptics as well as outreach about Covid-19 with a total expenditure of IDR 55,837,403. The next principle is a systematic and adaptive approach, through the activities carried out is the creation of a quarantine place. By spending Rp. 10,920,000. And the last principle is Simple design and continuous, through activities to sterilize the Jorong environment by spending Rp. 19,480,000. Keywords: Role, Agile Governance, Nagari Government, Covid-19 Countermeasures